Validation of optogenetic protein expression in the Dorsal cochlear nucleus: molecular basis for in vitro and in vivo investigation of tinnitus in mice - Borges, Thawann Malfatti (2015)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES)